Diabetes mellitus and heart diseases - Afa Bayramova (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2018)
Diabetes mellitus is recognized by World Health Organisation experts as a non-communicable epidemic and represents a serious medical and social problem. In 2012, suffered of diabetes mellitus about 6.4% (285 million) of the world's inhabitants. By 2030, the number of patients is expected to increase to 7.7% (439 million people) [1]. Coronary heart disease is the leading cause of death in patients with diabetes [2], with 90% of these patients suffering from type 2 diabetes (diabetes mellitus 2) [3]. The presence of diabetes is associated with the emergence of all forms of coronary heart disease - angina pectoris, painless myocardial ischemia, myocardial infarction, sudden cardiac death [4]. At the same time, macrovascular complications, including coronary heart disease, stroke, peripheral vascular disease, are the cause of death of patients with diabetes in 67% of cases [5]. In 50% of cases, the increased risk of developing cardiovascular lesions in diabetes mellitus 2 is due to the greater frequency and severity of traditional risk factors in diabetic patients [6,7]. Risk factors in patients with diabetes are: dyslipidemia, arterial hypertension, smoking, hereditary predisposition for coronary heart disease, the presence of micro- and macroalbuminuria.